Stent-graft placement for delayed extrahepatic portal hemorrhage after surgical treatment for perihilar cholangiocarcinoma: A case report. (2020) - Tsukamoto, Tadashi; Nobori, Chihoko; Nishiyama, Tsuyoshi; Kunimoto, Tomohiro; Kaizaki, Ryoji; Inoue, Toru; Nishiguchi, Yukio
Highlights: Stent-graft placement is a viable option for treatment of portal vein hemorrhage. Postoperative hemorrhage was caused by extrahepatic portal vein pseudoaneurysm formation. Portal vein pseudoaneurysm occurred at the reconstructed portion. Abstract: Introduction: Potential curative therapy for perihilar cholangiocarcinoma requires extensive surgical treatment, which can still be associated with significant morbidity and mortality. Postoperative hemorrhage from the portal vein is a rare but life-threatening complication. We herein report postoperative hemorrhage from an extrahepatic portal vein pseudoaneurysm successfully treated by stent graft placement late after surgical treatment for perihilar cholangiocarcinoma. Presentation of case: An 83-year-old man was referred to our hospital with a chief complaint of jaundice. Based on radiological findings, we diagnosed the patient with hilar cholangiocarcinoma. After endoscopic retrograde biliary drainage, resection of the extrahepatic bile duct combined with extended left hemi-hepatectomy, including the caudate lobe, lymphadenectomy of the hepatoduodenal ligament, partial resection and reconstruction of the portal vein, and right hepaticojejunostomy was performed. Fourteen days postoperatively, bleeding through the abdominal drain around the portal vein was observed. Twenty days postoperatively, abdominal computed tomography revealed a portal vein pseudoaneurysm that had formed at the portion of reconstruction. Therefore, 24 days postoperatively, a stent graft placement of the pseudoaneurysm through the ileocolic vein was performed. Subsequently, the portal vein hemorrhage ceased. Discussion: Our present postoperative extrahepatic portal vein hemorrhage case was caused by an extrahepatic portal vein pseudoaneurysm that had formed at the reconstructed portion by erosion due to the chemical effect of the leaking bile and mechanical irritation of the surgical drain adjacent to the portal vein. Conclusion: Stent-graft placement is a minimally-invasive, safe, and effective treatment option for hemorrhage from postoperative portal vein pseudoaneurysm.